Application Specific Integrated Circuits Technologies, Digital Systems and Design Methodologies - Fisher, Edward (IntechOpen, 2019)
The field of application-specific integrated circuits (ASICs) is fast-paced being at the very forefront of modern nanoscale fabrication-and presents a deeply engaging career path. ASICs can provide us with high-speed computation in the case of digital circuits. For example, central processing units, graphics processing units, field-programmable gate arrays, and custom-made digital signal processors are examples of ASICs and the transistors they are fabricated from. We can use that same technology-complementary metal-oxide semiconductor processes-to implement high-precision sensing of or interfacing to the world through analog-to-digital converters, digital-to-analog converters, custom image sensors, and highly integrated micron-scale sensors such as magnetometers, accelerometers, and microelectromechanical machines. ASIC technologies-now transitioning toward magneto-resistive and phase-changing materials-also offer digital memory capacities that have aided our technological progress. Combining these domains, we have moved toward big data analytics and the new era of artificial intelligence and machine learning. This book provides a small selection of chapters covering aspects of ASIC development and the surrounding business model.